The effect of pro-inflammatory cytokines on the development of atherosclerosis in systemic lupus erythematosus patients: ultrasonographic assessment of intimal medial thickness and resistive index - Mohamed Nasser; Mary Wadie; Alyaa Farid; Azza El Amir (Egyptian Rheumatology and Rehabilitation)
Abstract Background Systemic lupus erythematosus (SLE) is a debilitating rheumatic condition that results in the dysfunction of multiple organs in the body. Atherosclerosis is a common occurrence in people with SLE and is exacerbated by an overabundant of various cytokines, such as tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6), and their soluble receptors, such as soluble tumor necrosis factor receptor I (sTNFR I) and soluble interleukin-6 receptor (sIL-6R) (known as SLE risk factors) and high concentrations of lipids (known as dyslipidemia risk factors). The intimal medial thickness (IMT) of the internal carotid artery (ICA) is a sonographic measurement that assesses the extent of atherosclerosis. On the other hand, the resistive index (RI) is primarily employed to evaluate the severity of chronic kidney diseases (CKDs), but it is seldom utilized to estimate atherosclerosis in ICA. So, the objective of this study was to conduct retrospective cohort study among SLE patients to define which risk factor, inflammation or dyslipidemia, correlated with the development of atherosclerosis in SLE and which ultrasound assessment, CIMT or RI, is more useful in identifying atherosclerosis. Results TNF-α, sTNFR I, IL-6, and sIL-6R were significantly elevated (P < 0.0001) in SLE patients (n = 75) compared to the controls (n = 15); also, both CIMT and RI showed significant higher levels in patient’s group (P = 0.001 and 0.0025, respectively). Systemic lupus disease activity index (SLEDAI) (P = 0.002), total cholesterol (TC) (P = 0.025), CIMT (P = 0.00045), TNF-α (P < 0.0001), IL-6 (P < 0.0001), sTNFR I (P = 0.006), and sIL-6R (P < 0.0001) rates were significantly higher in atherosclerotic SLE patients (n = 27) than in non-atherosclerotic patients (n = 48). There were clear and meaningful positive correlations (r = 0.82, P = 0.003) observed between CIMT and SLEDAI, as well as between investigated cytokines and their soluble receptors. RI showed no significant differences between two studied groups of patients and also no significant correlations with the studied parameters except with age (r = 0.45, P = 0.035). Conclusion Inflammation is a more prevalent cause of atherosclerosis than dyslipidemia in SLE, thereby making it a recognized risk factor for SLE. In comparison to RI, CIMT is a valuable sonographic measure for identifying incidence of atherosclerosis.